Study on the References of Architectural Heritage Adaptive Reuse - Laretna Trisnantari Adishakti; Dimas Wihardyanto; Ikaputra Ikaputra; Dwita Hadi Rahmi; Dyah Titisari Widyastuti; Alyas Abibawa Widita (Jurnal Arsitektur, 2023)
Heritage Architectural Design or Olah Desain Arsitektur Pusaka (ODAP) in Bahasa Indonesia, has several names including adaptation architecture, filler architecture or infill design. ODAP is a method of architectural preservation that is carried out by grafting in new activities, and/or adding buildings either in part or in whole by first carrying out an in-depth study. As a method of preserving heritage, ODAP cannot separate itself from utilization strategies. This is because the preservation of architectural heritage will be meaningless if it is not able to provide benefits from a social, cultural and or economic perspective. Even further, it can become a source of new creativity in the field of architecture, arts and culture and its economic value. In order to achieve this, heritage conservation actors and related parties are required to have good sensitivity, taste, and creativity and have the desire to always develop. In this article, we will examine this ODAP, and how its role is to provide guidelines and considerations in design decisions for a heritage architecture so that it can be useful again in the future.